2018
DOI: 10.1097/md.0000000000013727
|View full text |Cite
|
Sign up to set email alerts
|

ED50 and ED95 of intrathecal hyperbaric ropivacaine for parturients undergoing cesarean section with prophylactic infusion of phenylephrine

Abstract: Background:Studies have reported that the ED50 of intrathecal ropivacaine was increased when using prophylactic infusion of phenylephrine to prevent spinal-induced hypotension. However, ED95 is more meaningful to clinical practice than ED50. Therefore, we conducted this study to determine the 95% effective dose (ED95) of intrathecal hyperbaric ropivacaine for cesarean section in parturients receiving prophylactic infusion of phenylephrine to prevent spinal-induced hypotension.Methods:A hundred of healthy partu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…There were no restrictions based on the type of neuraxial anaesthesia used. In addition, studies were excluded that utilised unclear methodology; administered neuraxial anaesthesia doses < ED95, as reported by Ginosar et al and Xu et al (ED95 doses reported as ≥ 11.2 mg intrathecal bupivacaine [12] or ≥ 15.2 mg ropivacaine [13]); or where a block height less than a T6 level was achieved when epidural anaesthesia was used [14]. If block height was not reported in a study using epidural anaesthesia, the study was excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no restrictions based on the type of neuraxial anaesthesia used. In addition, studies were excluded that utilised unclear methodology; administered neuraxial anaesthesia doses < ED95, as reported by Ginosar et al and Xu et al (ED95 doses reported as ≥ 11.2 mg intrathecal bupivacaine [12] or ≥ 15.2 mg ropivacaine [13]); or where a block height less than a T6 level was achieved when epidural anaesthesia was used [14]. If block height was not reported in a study using epidural anaesthesia, the study was excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary aims were to estimate the prevalence of conversion of neuraxial to general anaesthesia and to compare the prevalence of inadequacy between different modes of anaesthesia. [12] or ≥ 15.2 mg ropivacaine [13]); or where a block height less than a T6 level was achieved when epidural anaesthesia was used [14]. If block height was not reported in a study using epidural anaesthesia, the study was excluded.…”
Section: Introductionmentioning
confidence: 99%
“…It is prudent to monitor that the total dose of the injected AL does not exceed the recommended total dose to avoid local neurotoxicity, or anesthetic effects. If possible, it is recommended that another type of LA be injected in the second subarachnoid puncture [12][13][14][15].…”
Section: Alpha2 Agonistsmentioning
confidence: 99%
“…Thus small dose of local anesthestic was advocated due to low incidence of hypotension induced by SA, however it possibly increased the failures [8,9]. In some cases phenylephrine has to be administered because of its' more advantages to prevent SA related to hypotension [5,10].…”
mentioning
confidence: 99%